Tools for Teacher Training: Community Leadership, Mentoring Networks, and Learning Communities - Celedón-Lacayo, Tirso; Malespín, Álvaro; Romero, Miroslava (Scientific journal of social studies, 2023)
For effective teacher training, it is essential to promote their training and provide them with the necessary tools for proper educational management. The availability of relevant and pertinent tools is key to developing educational work that meets the needs of both students and society in general. Leadership is a broad and multifaceted topic that has been studied in various contexts, including education. The present study consists of a literature review about the information available as an approach to an educational strategy based on these concepts and how they can influence the performance and development of students, teaching staff and the operation of educational institutions. It is considered that teachers and social leaders seek to achieve educational objectives, developing tutoring networks as an innovative strategy to fill the gaps in learning communities.